A qualitative study of university students' experience of Internet‐based CBT for depression. Issue 4 (17th August 2021) - Gericke, Franco; Ebert, David D.; Breet, Elsie; Auerbach, Randy P.; Bantjes, Jason
Abstract: Internet‐based treatments for depression have the potential to promote the mental health of university students. Yet, little is known about students' experiences of Internet‐based mental health interventions (also known as e‐interventions) and the acceptability of this mode of treatment in low‐resource settings. Our aims were to investigate South African university students' experiences of using a brief semi‐guided Internet‐based cognitive behavioural therapy (iCBT) for depression and document the acceptability of this mode of psychotherapy. Data were collected via in‐depth semi‐structured interviews with students ( n  = 9) who had moderate to moderately severe symptoms of depression (as assessed by the PHQ‐9) and had used a 7 session guided skills‐based iCBT intervention. Data were analysed inductively using thematic analysis, with the aid of Atlas‐ti software. Participants found the anonymity, privacy and accessibility of iCBT appealing, believing this facilitated use of the intervention and overcame stigma associated with accessing traditional campus counselling services. The intervention was helpful and facilitated self‐disclosure, emotional expression, self‐awareness and skill acquisition. However, students also reported disappointment with the lack of human contact and immediate responsiveness, articulating an expectation that the e‐intervention would mimic face‐to‐face psychotherapy. Moves to incorporate iCBT into student counselling should take account of and manage students' expectations about the ability of e‐interventions to mimic traditional therapy and/or incorporate more opportunities for human interaction.